Application of thermal lens technique to measure the thermal diffusivity of biodiesel blend - Sadrolhosseini, Amir Reza; Muhammad Noor, Ahmad Shukri; Mehdipour, Lotf Ali; Noura, Amin; Mahdi, Mohd Adzir (Springer Verlag, 2015)
Thermal diffusivity of palm biodiesel blends was measured using a thermal lens double beam setup. Palm biodiesel blends were prepared from a mixture of normal palm oil biodiesel and diesel fuel with the percentage of the mixture set in the range of 10–90 %. The thermal diffusivity of the palm biodiesel blends consistently increased by increasing the concentration of palm biodiesel from 0.784 × 10−7 to 1.056 × 10−7 m2/s and average of measurement limitation was 0.629 × 10−7 m2/s. Hence, thermal lens technique is suitable and accurate to assess the thermal diffusivity of palm biodiesel.